Making sense of fidelity: young Africans' cross-national and longitudinal representations of fidelity and infidelity in their HIV-related creative narratives, 1997–2014. Issue 1 (1st January 2021) - Singleton, Robyn; Billaud, Manon; McLeod, Haley; Tiendrebeogo, Georges; Dia, Fatim; Obong'o, Chris; Nkambule-Vilakati, Siphiwe; Mbakwem, Benjamin; Sabben, Gaelle; Winskell, Kate
ABSTRACT: Mutual fidelity and partner reduction have been identified as key behavioural strategies to prevent HIV transmission in sub-Saharan Africa, particularly following recognition of the role that multiple concurrent sexual partnerships play in driving generalised HIV epidemics. We analysed social representations of fidelity and infidelity in a sample of 1, 343 narratives about HIV written by young Africans between 1997 and 2014. The narratives were written at four different time points (1997, 2005, 2008, 2014) by authors aged 10–24 in urban and rural areas of Senegal, Burkina Faso, South-east Nigeria, Kenya and Eswatini. We combined three analytical approaches: descriptive statistics of quantifiable characteristics of the narratives, thematic data analysis and a narrative-based approach. In the sample, fidelity is often promoted as the ideal by narrators, peers and romantic partners, in line with broader discourses around HIV prevention, romantic relationships, familial obligations, and religious and moral imperatives. However, mutual fidelity is rarely modelled in the narratives and representations of combining methods to prevent HIV from entering relationships via infidelity are uncommon. Representations of fidelity reflect loss-framed fear arousal techniques that perpetuate HIV-related stigma. Narrative-based approaches that facilitate skills-building, critical reflection and address stigma can better address fidelity and partner reduction.